Reestructuración técnica del área de subensambles para la línea de producción de Montaje A en Marcopolo S.A. (2018)
Technical reorganization in sub-assembly area of Montaje A, developed in Marcopolo S.A., company works as car body manufacturing of small and big buses, wherein the line of buses Paradiso G7 1200 was taken as reference, to evaluate currently conditions of company and its environment, through of Porter’s Five Forces and Bogota’s Chamber of Commerce self-testing for creating strategies in DOFA matrix. It develops a technical study to establish improvement actions that permit an optimal development in the process, through a decrease of time and movements, capacity study, production plan and stock improvement, besides of proposal of healthy and safety elements in this area. Finally, in order to determinate the viability of this project, it makes a comparison between currently and proposal costs through financial tool named EAC (Equivalent Annual Cost), wherein shows the operation savings.